Integrating value systems and place-based characteristics in climate risk assessments - Reveco, Cristóbal; Cortekar, Joerg; Trozzo, Chiara; Vokral, Martin; Kotova, Lola; Kuntsi-Reunanen, Eeva; Galluccio, Giulia; Korhonen, Natalia (Frontiers in Climate, 2025)
This article examines how value systems and place-based characteristics shape the ways in which local communities define, represent and prioritise climate risks in urban and rural settings. Drawing on 10 climate impact-chain assessments—co-developed through participatory processes with stakeholders in demonstration regions across Europe within the EU project VALORADA—we explore four hazard domains: urban warming, heatwaves, droughts and extreme precipitation. Building on previous literature and based on our observations, we show that the identification, definition and prioritisation of climate risks extend beyond biophysical aspects or existential threats and are also influenced by locally salient values, including sustainability, security, safety, identity, human health, cooperation and trust. These values can, at times, come into tension—particularly where the management of scarce resources (e.g., water) is contested, or where policy goals such as environmental conservation and economic development intersect within the same decision arena. We conclude by suggesting that addressing the challenge of integrating value-based and place-specific characteristics into climate risk assessments may benefit from illustrating how climate hazards influence local value frameworks and shape meaningful societal participation.